2003
DOI: 10.1007/s11746-003-0730-0
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of FA profile obtained by high‐resolution GC/chemometric techniques to the authenticity of green and roasted coffee varieties

Abstract: Twenty-four coffee samples of different botanical and geographical origins were analyzed for their FA composition, including trans isomers. The analysis used high-resolution GC/FID/CP Sil 88 capillary column to separate FAME obtained by esterification with BF 3 /methanol. The purpose of this work was to verify whether this parameter could be applied in the discrimination of arabica and robusta coffees, either in green or in roasted stage. Statistical approaches were applied to check the efficiencies of some un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 12 publications
7
30
0
3
Order By: Relevance
“…Casal et al (1997) and then Alves et al (2003) reported that in Arabica and Robusta coffee the roasting process increased the trans-fatty acid levels, specifically the contents of C 18:2ct and C 18:2tc .…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Casal et al (1997) and then Alves et al (2003) reported that in Arabica and Robusta coffee the roasting process increased the trans-fatty acid levels, specifically the contents of C 18:2ct and C 18:2tc .…”
Section: Fatty Acidsmentioning
confidence: 99%
“…It is also used to quantify and classify metabolites in cereal plants such as maize, rice, wheat, barley, rye, and oats (Khakimov et al, 2014). Chemometric analysis is necessary for extraction of the molecular signatures of adulterants present in the sample (Alves et al, 2003;Reid et al, 2004). This adds to the labor, expertise, and time required for analysis and is the most common drawback for this technique (Cao et al, 2013).…”
Section: Conventional Methods Used To Detect Adulterants In Cereal Fomentioning
confidence: 99%
“…The profile of fatty acids can be used as tracer of a cultivar and can inform about the main qualities of the coffee (Alves et al, 2003). The fatty acids play a role in a series of catabolic reactions that lead to the production of compounds of flavor and aroma typical in food (Collins et al, 2003), and have capacity to cover the tongue during the digestion, providing an fatty and creamy buccal sensation, typical of the body of the drink.…”
Section: Principal Component Analysismentioning
confidence: 99%